A combination of UV-Vis spectroscopy and chemometrics for detection of sappanwood (Caesalpinia sappan) adulteration from three dyes - Batubara, Irmanida; SaadatulHusna; Rafi, Mohamad; Sumaryada, Tony; Uchiyama, Susumu; Juliandi, Berry; Sastia Prama Putri; Fukusaki, Eiichiro (Penerbit Universiti Kebangsaan Malaysia, 2022)
Sappan wood (Caesalpinia sappan) is very well known as a natural dye for traditional food and beverage in many countries. Recently, there are many reports of sappan wood adulteration by adding synthetic or natural dyes to obtain quality color and better appearance. In this study, UV-Vis absorption spectra coupled with chemometrics were used to develop rapid detection of sappan wood raw material adulteration (authentication) from three dyes, i.e., sudan III, commercial textile dyes, and red yeast rice. Absorption spectra of 13 sappan wood raw material and adulterated sappan wood with the three dyes in two different concentrations which resulted about 78 adulterated samples were measured with UV-Vis spectrophotometer at a wavelength range of 200-800 nm. A principal component analysis followed by discriminant analysis was used to construct a model for the authentication of sappan wood from the three dyes used in this study. The combination of both methods was successfully classified sappan wood as non-adulterated and adulterated with the dyes. Cross-validation results of the authentication model of sappan wood from sudan III, commercial textile dyes, and red yeast rice were 94.12%, 94.12%, and 92.16% correctly classified into their groups, respectively.